2018
DOI: 10.1071/rd17431
|View full text |Cite
|
Sign up to set email alerts
|

Sperm morphology of the Rattini – are the interspecific differences due to variation in intensity of intermale sperm competition?

Abstract: It is widely accepted that in mammals a causal relationship exists between postcopulatory sexual selection and relative testes mass of the species concerned, but how much it determines sperm size and shape is debatable. Here we detailed for the largest murine rodent tribe, the Rattini, the interspecific differences in relative testes mass and sperm form. We found that residual testes mass correlates with sperm head apical hook length as well as its angle, together with tail length, and that within several line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
1
18
1
Order By: Relevance
“…There seems to be coevolution between sperm form and sperm size. Thus, an increase in sperm head complexity is accompanied by an increase in total sperm length, as originally pointed out by our group (Roldan, Gomendio, & Vitullo, ), and both are coevolving under the influence of sperm competition (Breed et al., ; McLennan et al., ; Pahl et al., ).…”
Section: Diversity In Sperm Numbers and Morphology And Underlying Sesupporting
confidence: 68%
See 1 more Smart Citation
“…There seems to be coevolution between sperm form and sperm size. Thus, an increase in sperm head complexity is accompanied by an increase in total sperm length, as originally pointed out by our group (Roldan, Gomendio, & Vitullo, ), and both are coevolving under the influence of sperm competition (Breed et al., ; McLennan et al., ; Pahl et al., ).…”
Section: Diversity In Sperm Numbers and Morphology And Underlying Sesupporting
confidence: 68%
“…the so‐called hook) also shows that both its length and angle are influenced by sperm competition (Immler, Moore, Breed, & Birkhead, ; Varea‐Sánchez, Tourmente, Bastir, & Roldan, ). A series of recent comprehensive analyses of Australian rodents, a group in which several appendices have evolved in the sperm head, showed that several head parameters associate with levels of sperm competition (Breed et al., ; McLennan, Lüpold, Smissen, Rowe, & Breed, ; Pahl et al., ).…”
Section: Diversity In Sperm Numbers and Morphology And Underlying Sementioning
confidence: 99%
“…The coevolution of male and female reproductive proteins may be associated with the eventual development of barriers to fertilization, reproductive isolation, and subsequent speciation ( Swanson and Vacquier 2002 ). There is substantial divergence in sperm morphology between closely related murine species (e.g., Breed 2000 ; McLennan et al 2017 ; Pahl et al 2018 ), which may contribute to the rapid evolution of prezygotic isolation between populations. Accelerated evolution, or increased positive selection, in reproductive genes in murine rodents may be linked, in part, to the rapid speciation of murines in both allopatry, and via ecological niche partitioning in spatially limited island systems.…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 7, 2020. ; https://doi.org/10.1101/2020.12.05.413120 doi: bioRxiv preprint hooks that vary in their length and curvature [3,[7][8][9]. For sperm head designs that are complex, identifying and quantifying informative morphological features and, thus, their functional significance has been an ongoing challenge across taxa [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%